ANALISIS SWOT D’VUL RERSTAURANT AND CAFE DI LOMBOK INTERNATIONAL AIRPORT DALAM UPAYA MENDUKUNG PENGHARGAANWORLD’S BEST HALAL HONEYMOON DESTINATION AND WORLD’S BEST HALAL TOURISM DESTINATION - muhammad habibullah aminy (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2018)
SWOT analysis is one way to determine the business strategy used for planning, organizing, actuating, and controlling (POAC) business strategies in the long and short term. From the description above, the researcher tried to examine the "SWOT Analysis of the Dul Rerstaurant And Cafe at Lombok International Airport in an effort to support the World’s Best Halal Award. Honeymoon Destination And World’s Best Halal Tourism Destination". The purpose of the SWOT analysis is to find out the strengths, weaknesses, opportunities and threats that are owned and or faced by the company. The research method used was descriptive qualitative with data collection techniques using observation, interviews and documentation, the location of this study was at Lombok International Airport, Praya, Central Lombok Regency, NTB. The results of the strength factor were greater than the weaknesses owned by D’Vul restaurant and cafe and the opportunity factor was also greater than the threat factor. Therefore, with conditions like this, D'Vul restaurant and cafe should be able to compete with other restaurants and cafes around Lombok International Airport and have been able to participate in supporting Lombok as the World's Best Halal Honeymoon Destination and World's Best Halal Tourism Destination